Chronic kidney disease and cardiac morbidity — What are the possible links?. (June 2016) - Freundlich, Michael; Lipshultz, Steven E.; Filler, Guido
Abstract: It is increasingly clear that the long-term outcome of children with chronic kidney disease (CKD) is associated with their cardiovascular outcomes. Renal dysfunction affects cardiovascular outcomes, and cardiovascular dysfunction affects renal outcomes. Despite many publications about cardio-renal syndrome (CRS) types I to III (acute CRS, chronic CRS and acute renocardiac syndrome), the literature about type IV CRS (chronic renocardiac syndrome) remains scant. Here, we summarize the pathophysiological risk factors of cardiovascular comorbidity and CKD. We address the exceedingly high prevalence of cardiovascular morbidity and mortality in children and adolescents with CKD and their risk factors for cardiovascular disease (CVD). Of these risk factors, uremia, renal osteodystrophy, vitamin D pathophysiology, and Fibroblast Growth Factor 23 (FGF23)-related direct effects on the myocardium and the large vessels appear to be the most prominent. We identify potential targets for intervention and highlight the need for a multidisciplinary approach involving both pediatric cardiologists and nephrologists.